Considering digits in a current model of numerical development - Roesch, Stephanie; Moeller, Korbinian (Frontiers in Human Neuroscience, 2015)
Numerical cognition has long been considered the perfect example of abstract information processing. Nevertheless, there is accumulating evidence in recent years suggesting that the representation of number magnitude may not be entirely abstract but might present a specific case of embodied cognition rooted in the sensory and bodily experiences of early finger counting and calculating. However, so far none of the existing models of numerical development considers the influence of finger-based representations. Therefore, we make first suggestions on (i) how finger-based representations may be integrated into a current model of numerical development and (ii) how they might corroborate the acquisition of basic numerical competencies at different development levels.